2018
DOI: 10.14419/ijet.v7i3.36.29206
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production from Combined Irish Potato and Poultry Wastes: Optimization and Kinetic Studies

Abstract: The combination of Irish potato waste (IPW) and poultry waste (PW) can form a synergy resulting into an effective substrate for a better biogas production due to some materials they contain. In this work, optimization and kinetic study of biogas production from anaerobic digestion of IPW and PW was investigated. Response surface methodology (RSM) was applied to optimize conditions such as initial pH, solids concentrations and waste ratios. The anaerobic digestion of the two wastes was carried out in the mesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The biogas produced is valuable waste from sludge disposal and is of outstanding quality. Since substrates are obtained for free while protecting flora and fauna against harmful effects of wastewater, biogas plants at sewage treatment plants are the best solution for biogas production [40]. Biogas production in wastewater treatment plants (WWIPs) plays a decisive role in reducing CO 2 emissions and energy needs in the context of the waterenergy nexus [41][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…The biogas produced is valuable waste from sludge disposal and is of outstanding quality. Since substrates are obtained for free while protecting flora and fauna against harmful effects of wastewater, biogas plants at sewage treatment plants are the best solution for biogas production [40]. Biogas production in wastewater treatment plants (WWIPs) plays a decisive role in reducing CO 2 emissions and energy needs in the context of the waterenergy nexus [41][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…66, No. 9 (2023) authors used the granite in different sources as powder waste from sawing processes of ornamental stones, fresh and weathered rocks in the ceramic tile industries and concluded that about 15-40 % of granite can be used for the production of red stoneware tiles using rapid-firing cycles and fired at 1200-1300°C [18][19]. Granite is considered a flux material due to its large amount of alkali oxides as K2O and Na2O.…”
Section: Introductionmentioning
confidence: 99%
“…The stages of acetogenesis and methanogenesis responsible for the production of methane, called "methanogenic fermentation", are also related [21]. Hence, there is often a reference to a two-stage process of anaerobic conversion of organic matter [22]. The fermentation process functions best when the rate of decomposition of organic matter in the acidic and methane-fermentation stages is the same.…”
Section: Introductionmentioning
confidence: 99%